Population Dynamics and Diversity of Viruses, Bacteria and Phytoplankton in a Shallow Eutrophic Lake - Tijdens, Marjolijn (Springer-Verlag, 2007)
We have studied the temporal variation in viral abundances and community assemblage in the eutrophic Lake Loosdrecht through epifluorescence microscopy and pulsed field gel electrophoresis (PFGE). The virioplankton community was a dynamic component of the aquatic community, with abundances ranging between 5.5 × 10(7) and 1.3 × 10(8) virus-like particles ml(−1) and viral genome sizes ranging between 30 and 200 kb. Both viral abundances and community composition followed a distinct seasonal cycle, with high viral abundances observed during spring and summer. Due to the selective and parasitic nature of viral infection, it was expected that viral and host community dynamics would covary both in abundances and community composition. The temporal dynamics of the bacterial and cyanobacterial communities, as potential viral hosts, were studied in addition to a range of environmental parameters to relate these to viral community dynamics. Cyanobacterial and bacterial communities were studied applying epifluorescence microscopy, flow cytometry, and denaturing gradient gel electrophoresis (DGGE). Both bacterial and cyanobacterial communities followed a clear seasonal cycle. Contrary to expectations, viral abundances were neither correlated to abundances of the most dominant plankton groups in Lake Loosdrecht, the bacteria and the filamentous cyanobacteria, nor could we detect a correlation between the assemblage of viral and bacterial or cyanobacterial communities during the overall period. Only during short periods of strong fluctuations in microbial communities could we detect viral community assemblages to covary with cyanobacterial and bacterial communities. Methods with a higher specificity and resolution are probably needed to detect the more subtle virus–host interactions. Viral abundances did however relate to cyanobacterial community assemblage and showed a significant positive correlation to Chl-a as well as prochlorophytes, suggesting that a significant proportion of the viruses in Lake Loosdrecht may be phytoplankton and more specific cyanobacterial viruses. Temporal changes in bacterial abundances were significantly related to viral community assemblage, and vice versa, suggesting an interaction between viral and bacterial communities in Lake Loosdrecht.